ANALISIS EFEKTIVITAS ORGANISASI KANTOR UNIT PELAKSANA TEKNIS DINAS (UPTD) PERWAKILAN KABUPATEN TOLITOLI DI KOTA PALU - Kasim, Muhajir A. (Katalogis, 2015)
This study aims at analyzing the Organizational effectiveness on the Office of Technical Implementation Unit (UPTD) of Tolitoli Representative in Palu using qualitative descriptive analysis. Informants of this research are the officers in Technical Implementation Unit Office (UPTD) of Tolitoli Representative, other associated institutions and staying guests, which are determined purposively with data collection methods consisted of observation, interviews and documentation, while the technique of data analysis includes data reduction, data display and drawing conclusions and verification. Results of the research show that the organizational effectiveness of the UPTD office of Tolitoli representative has not been completely worked well yet, due to several factors of organizational effectiveness which are not executed, i.e. the factor of organizational characteristic where in the arrangement of the organizational structure, it is necessary to repair or realignment by adding some level of departemenization for grouping tasks and responsibility into multiple unit/section, environmental characteristics, namely internal environment, especially the provision of office facilities and accommodation needs to be recovered and revamped to improve the quality of service, and to its external environment in terms of the relationship with the institutions in the capital of Central Sulawesi province is already running well. The officers characteristics, considering the human resources, need to be increased in terms of capability and expertise through education, training and courses, as well as the implementation of policies and management practices needs to set up the Operational Procedures Standard (SOP) and the Minimum Service Standards (SPM) to improve the quality of service to the organizational effectiveness.